2000
DOI: 10.1038/80819
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of inflammatory chemokine receptors by IL-10: generation of functional decoys

Abstract: As originally demonstrated for the interleukin 1 (IL-1) type II receptor, some primary proinflammatory cytokines from the IL-1 and tumor necrosis factor families are regulated by decoy receptors that are structurally incapable of signaling. Here we report that concomitant exposure to proinflammatory signals and IL-10 generates functional decoy receptors in the chemokine system. Inflammatory signals, which cause dendritic cell (DC) maturation and migration to lymphoid organs, induce a chemokine receptor switch,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
155
2

Year Published

2002
2002
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 235 publications
(163 citation statements)
references
References 46 publications
6
155
2
Order By: Relevance
“…IL-10 was previously shown to impact DC migration negatively in vivo through its specific down-regulation of CCR-7 expression [41]. A study by D'Amico et al revealed that concomitant exposure to IL-10 completely blocks the LPS-induced chemokine receptor switch associated with DC maturation [35]. Therefore, the up-regulated production of IL-10 by db/db DC may contribute to the observed alteration in chemokine receptor expression.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…IL-10 was previously shown to impact DC migration negatively in vivo through its specific down-regulation of CCR-7 expression [41]. A study by D'Amico et al revealed that concomitant exposure to IL-10 completely blocks the LPS-induced chemokine receptor switch associated with DC maturation [35]. Therefore, the up-regulated production of IL-10 by db/db DC may contribute to the observed alteration in chemokine receptor expression.…”
Section: Discussionmentioning
confidence: 98%
“…There is compelling evidence that IL-12 production is also affected by cross-regulation between different DC subsets, involving cytokines such as IL-10 and type I IFN [34,35]. Thus, the marked reduction of IL-12p70 secretion by db/db DC may result from increased IL-10 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the downregulation of CCR5 ligands, the receptor itself is upregulated in vitro and in vivo. A possible explanation for these contradictory results might be the recent observation, that these up-regulated receptors have only a scavenging effect but are unable to signal [20]. Noticeably, there is a strong down-regulation of the CCR6 ligand CCL20 (Exodus), a chemokine which has been observed to be up-regulated in psoriasis [21].…”
Section: Chemokinesmentioning
confidence: 99%
“…The significance of this observation may in fact relate to the effect of this cytokine when combined with primary proinflammatory signals (34). It was observed that IL-10 blocks down-regulation of inflammatory chemokine receptors induced by LPS alone or in combination with IFN-c in monocytes and dendritic cells.…”
Section: Regulation Of Receptor Expression and Couplingmentioning
confidence: 99%